Clinical, genetic, and epidemiological survey of Polish children and adolescents with severe obesity: A study protocol of the Polish–German study project on severe early-onset obesity - Mierzwa, Magdalena; Bik-Multanowski, Mirosław; Ranke, Michael B.; Brandt, Stephanie; Flehmig, Bertram; Małecka-Tendera, Ewa; Mazur, Artur; Petriczko, Elżbieta; Wabitsch, Martin; Wójcik, Małgorzata; Zachurzok, Agnieszka (Frontiers in Endocrinology, 2022)
Severe early-onset obesity (SEOO) in children is a common feature of monogenic obesity. Nowadays mutations in at least 50 genes are known to be related to monogenic obesity, and many others are tested. Part of them is involved in the leptin-proopiomelanocortin pathway. The aim of the project is to establish the Polish database of severely obese children and adolescents and to evaluate the prevalence of monogenic forms of obesity in this cohort, with a special focus on leptin-proopiomelanocortin pathway abnormalities. The secondary project aim is to identify new population-specific mutations in obesity-related genes in severely obese Polish children and adolescents. This is a prospective multi-center clinical study performed in four Polish centers. The estimated samples size is 500 patients aged 1 – 18 years, with severe obesity hyperphagia and food seeking behaviors. In each patient the medical history regarding the obesity duration in the patient and obesity and its complication existence in the family will be taken. Next the questionnaire regarding the symptoms characteristic for specific mutations, which we are going to test, will be performed. Hyperphagia will be assessed on the basis on age-specific questionnaires. The physical examination with anthropometric measurement, basic biochemical and hormonal tests as well as leptin and biologically active leptin measurements will be performed. Finally genetic analysis will be done using Next Generation Sequencing with sequencing libraries prepared to include obesity-related genes. The genotyping findings will be confirmed with the use of classic sequencing (the Sanger's method). In the future the pathogenicity of new mutations in obesity-related genes identified in our cohort is planned to be confirmed by functional testing in vitro. Nowadays there is no data regarding the prevalence of severe obesity or monogenic obesity in Polish children. This project has the potential to improve understanding of obesity etiology and may contribute to implement attribute mutation-specific treatment. Moreover, it may lead to a finding new, population-specific mutation related to SEOO.